Understanding Women's Experiences of Defending Against Eating Disorder Symptoms: An Interpretive Phenomenological Analysis. Issue 2 (October 2016) - Buser, Juleen K.; Parkins, Rachael A.; Salazar, Victoria
Abstract : Body dissatisfaction predicts eating disorder symptomatology for some women but not for others. To better understand this disparity, the authors interviewed 7 college women who reported body dissatisfaction and no engagement in eating disorder symptoms. The authors identified 4 factors that may protect body‐dissatisfied women from engaging in eating disorder symptoms.